Analysis of Teacher Performance in Improving the Learning Quality of Class XI TKJ Students at the Nias Adventist Vocational High School - Elfarida Sinaga; Laura Lahindah (Return : Study of Management, Economic and Bussines, 2024)
Education is the most important thing in the process of advancing a nation's civilization, with education, the exploration and empowerment of potential can be maximized to help direct humans to become better individuals. This research aims to analyze teacher performance in improving the quality of learning for class XI TKJ students at the Nias Adventist Vocational High School. The method used is a qualitative approach with data collection techniques through observation, interviews and documentation. The research variables consist of: teacher performance (x) and student learning quality (Y). The results of the analysis show that good teacher performance, characterized by careful learning planning, use of varied teaching methods, and positive interactions with students, contributes significantly to improving the quality of student learning. Apart from that, support for learning facilities and parent participation also play an important role in supporting the teaching and learning process. This research concludes that to improve the quality of student learning, there needs to be a synergy between teacher performance, school support and parental involvement.